Different sources and degradation state of dissolved, particulate, and sedimentary organic matter along the Eurasian Arctic coastal margin; Global Biogeochemical Cycles; Vol. 30, iss. 6 - Karlsson E. S.; Gelting J. Johan; Tesi T. Tommaso; van Dongen B. E.; Andersson A. August; Semiletov I. P. Igor Petrovich; Charkin A. N. Aleksandr Nikolaevich; Dudarev O. V. Oleg Viktorovich; Gustafsson O. Orjan (2016, 2016)
Title screen